ANALISI KANDUNGAN BORAK PADA JAJANAN BAKSO TUSUK DI SEKOLAH DASAR DI KECAMATAN BANGKINANG KABUPATEN KAMPAR. - Nurkholidah Nurkholidah; Mirna Ilza; Cristine Jose (Jurnal Ilmu Lingkungan, 2012)
School-age children is an investment of a nation and the growth depends on the intake offood. Currently there are still many foods that contain borax as the meatball skewers are soldfreely in the elementary schools sub district of Bangkinang. In addition it is alleged there isno control over school snacks both the government and the schools that need to be conductedstudies on the use of borax on meatball skewers. The research aims to determine the contentof borax and proximate analysis of the meatball skewers in sub district of Bangkinang, comparing the borax and nutritional content of meatball skewers which are made directly bythe merchant and the meatball skewers that are purchased from the manufacturer anddetermine the characteristics and motivations of merchant that using borax. Samples weretaken from 17 merchants who sell in the elementary schools sub district of Bangkinang asmuch as 3 times the sampling distance of 1 week and 3 times of observation. Based on theresearch the average characteristics of meatball merchant ages are 32,41 years old with 2.1years experience of selling and the duration of 5.24 hours a day with a turnover of Rp.268,680. High school and junior high school educated merchant make more own meatballswhich conceal the recipe and only 5.88% of merchant who ever got the attention of thegovernment. Merchants who sell meatball skewers at the elementary school generally usesborax. The content of borax ranged from 0.48 mg/g sample up to 2.32 mg/g sample. Thelargest average content of borax on meatball skewers obtained from the manufacturer. Thenutritional content of the protein content ranged from 0.18% to 1.58%. The water content between 28.84% to 64.12%. Fat content ranged from 0.62% to 8.74%. Ash content rangedfrom 1.61% to 5.01% and carbohydrates ranged from 30.94% to 59.24%. The highestaverage levels of fat, ash and carbohydrate levels are meatball made by merchants while thehighest protein and water contents obtained from meatball skewers manufacturer. Motivationof merchant use borax is obtained more chewy and durable meatballs texture so will result inhigher profits moreover the merchant do not know borax and dangers due to the lack ofgovernment attention.